STRUGGLE FOR BEING A FAIR LAWYER REFLECTED IN VINA DELMAR'S BELOVED: AN INDIVIDUAL PSYCHOLOGICAL APPROACH - AMALIA, NUR 'AINI (2007)
The problem of this study is how the major character's effort to get the future, as a lawyer reflected in Vina Delmar's Beloved. The objective of this study is to analyze Vina Delmar's Beloved based in the structural elements and to analyze the novel based on an individual psychological approach. The researcher employs qualitative method. In this study, the researcher uses two data sources, namely primary and secondary data sources. The primary data source is novel itself. The secondary data sources are books, internet and other sources, which are related to the novel. The technique of data collection is documentation of library research. Based on the analysis, the researcher finds that past experiences may give bad effect to someone. To compensate it, he/she tries to improve his/her ability, and becoming successful people.